Population dynamics of Labeo calhasu (Hamilton) in the Sylhet basin, Bangladesh - Alam, M; Amin, S M N; Haroon, A K Yousuf (Indian Journal of Fisheries, 2011)
Population parameters of Labeo calbasu (Hamilton) were estimated using FiSAT software with length-frequency data collected from different areas of Sylhet basin, north-eastern part of Bangladesh. The von Bertalanffy growth parameters LÂ°Â° and K for the species were 49.30 cm and 0.63 / year respectively. The annual rate of natural (M) and fishing (F) mortality were found to be 1.11 and 3.48, respectively. The rate of exploitation (E) was estimated as 0.76. Recruitmet of this species into the fishery takes place during August to October with peak during August- September. E^j^ was found to be 0.449. The present investigation clearly showed the over fishing (E>0.50) condition for L. calbasu in the Sylhet basin. The relationship between the total length and body weight was found to be W + 0.00927*TL 3.109.